PEMBELAJARAN STRATEGI PEMECAHAN MASALAH SISTEMATIS DAN WANKAT-OREOVOCZ BERBANTUAN METODE EKSPERIMEN DAN DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI OPTIK - IRSADA, FIAN (Jurnal Ilmu Pendidikan Indonesia, 2021)
The purpose of this study was to determine the interaction between the application of learning systematic problem solving solutions and Wanket-Oreovocz. Experimental and demonstration methods have different effects. The number of students in this study were 70 students who were divided into two classes, namely the application of systematic problem solving strategy learning which amounted to 34 students and the application of the Wanket-Oreovocz problem solving strategy class totaled 36 students in terms of the application of experiments and demonstrations. learning methods. Samples were taken using the purposive sampling technique. The research design used in this study is a factorial design. Data analysis using Anova technique with SPSS software version 16.0..Research results of data analysis in this research used to improve studentsâ€™ cognitive learning outcomes in terms of application of learning systematic troubleshooting strategy and demonstration method obtained 0.59 which was in moderate â€œcategoryâ€, the application of Wanket-Oreovocz troubleshooting strategy and experimental methods obtained 0.56 which was in moderate â€œcategoryâ€. Wanket-Oreovocz troubleshooting strategy that obtained 0.61 was also obtanined 0.61. Results hypothesis showed that there is difference in cognitive learning outcomes between the application of learning systematic troubleshooting strategy and Wanket-Oreovcz (sig-value 0.854 > 0,05); there are differences in cognitive learning outcomes between the application of experimental method and demonstration method (sig-value 0.035 < 0.05);and there is no interaction between systematic troubleshooting strategy and Wanket-Oreovcz, which demonstration method was better used than experiment method.